In Vitro Assessment of Cytokine Expression Profile of MCF-7 Cells in Response to hWJ-MSCs Secretome - Mansoureh Mirabdollahi; Shaghayegh Haghjooy Javanmard; Hojjat Sadeghi-Aliabadi (Tabriz University of Medical Sciences, 2019)
Purpose: Several attempts have been made to identify the mechanisms by which mesenchymal stem cells (MSCs)-derived secretome exert anti-tumor or tumorigenic effects, but still further investigations are needed to explore this subject. Thus, in this study we want to examine the expression of different cytokines in secretome of hWJ-MSCs and their effects on cytokine expression profile of the MCF-7 tumor cells. Methods: The hWJ-MSCs were isolated and characterized according to the International Society for Cellular Therapy criteria. Then, secretome of hWJ-MSCs was collected and freeze-dried, and 20 mg/mL of the freeze-dried secretome was used to treat MCF-7 cancer cells for 48 hours. Afterwards, the expression levels of 12 cytokines including IL-1a, IL-1b, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-17A, TNFα, IFNγ and GM-CSF in secretome of hWJ-MSCs alone as well as in supernatant of tumor cells before and after treatment with hWJ-MSCs secretome were evaluated. Results: Our results indicate that MCF-7 cells express significant amount of IL-6 and IL-8. Moreover, significant amounts of IL-1a, IL-1b, IL-8, IL-6 and GM-CSF were detected in secretome of hWJ-MSCs. Furthermore, IL-1a, IL-2 and IL-4 were expressed significantly by MCF-7 cells after their treatment with hWJ-MSCs-derived secretome. Conclusion: According to our findings, the hWJ-MSCs derived secretome contains different cytokines which can exert either anti-tumor or tumorigenic effects.